2022
DOI: 10.1055/s-0042-1759639
|View full text |Cite
|
Sign up to set email alerts
|

COVID-Associated Sinonasal Mucormycosis: Radiological Pathological Correlation and Prognostic Value of MR Imaging

Abstract: Purpose Our aim was to assess the sinonasal magnetic resonance imaging (MRI) features of acute invasive fungal rhinosinusitis (AIFRS) in coronavirus disease (COVID)-associated mucormycosis (CAM) and to correlate these with histopathology and patient outcome in terms of duration of hospital stay and survival at 10 weeks. Methods Twenty patients with histopathologically confirmed sinonasal CAM underwent MRI (including postcontrast T1-weighted and diffusion-weighted imaging). Histopathological findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In sinuses, Agarwal et al observed variable signal intensity on T2WI and predominantly (90%) hypointensity on T1WI (14). In our study, we also found variable signal intensity on T2WI (60% hyperintense, 25% isointense and 4% hypointense) and all showed hypointensity on T1WI.…”
Section: Tablesupporting
confidence: 80%
See 1 more Smart Citation
“…In sinuses, Agarwal et al observed variable signal intensity on T2WI and predominantly (90%) hypointensity on T1WI (14). In our study, we also found variable signal intensity on T2WI (60% hyperintense, 25% isointense and 4% hypointense) and all showed hypointensity on T1WI.…”
Section: Tablesupporting
confidence: 80%
“…In our study, we also found variable signal intensity on T2WI (60% hyperintense, 25% isointense and 4% hypointense) and all showed hypointensity on T1WI. The accumulation of hemosiderin and paramagnetic materials such as calcium, iron, magnesium, and manganese has been linked to hypointensity on T1WI and T2WI in fungal disease (3,14,15).…”
Section: Tablementioning
confidence: 99%
“…Regarding sinuses, Agarwal et al [ 14 ] observed variable signal intensity on T2WI and predominantly (90%) hypointensity on T1WI. In our study, we also found variable signal intensity on T2WI (60% hyperintense, 25% isointense, and 4% hypointense), and all showed hypointensity on T1WI.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also found variable signal intensity on T2WI (60% hyperintense, 25% isointense, and 4% hypointense), and all showed hypointensity on T1WI. The accumulation of hemosiderin and paramagnetic materials such as calcium, iron, magnesium, and manganese has been linked to hypointensity on T1WI and T2WI in fungal disease [ 2 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have described imaging features of COVID-19associated AIFR. 10,[13][14][15][16][17][18][19] We have described imaging findings in 90 studies including computed tomography (CT) and magnetic resonance imaging (MRI) of 60 patients of post-COVID-19 AIFR admitted and managed at our institute.…”
Section: Introductionmentioning
confidence: 99%